Penerapan Business Intelligence pada Data Cuaca Badan Meteorologi, Klimatologi, dan Geofisika (BMKG) - Melinda Andriyati; Soleh Ardiansyah; Muhammad Gilvy Langgawan Putra (SPECTA Journal of Technology, 2021)
As systems and methods that analyze data, Business Intelligence aims to gain insight. BMKG Kota Balikpapan has an obstacle in data management which takes almost two days. Data management consists of data processing, data analysis, data storage, and data accessing. BMKG Kota Balikpapan's problem can be answered by using Pentaho which is a proper tool for presenting the information from data management processes to gain knowledge. Business Intelligence implementation was performed by adopting a business intelligence roadmap: the business analysis phase, design phase, construction phase, and deployment phase. In conclusion, weather data processing into normal data by Pentaho has been done successfully. Normal data consists of normal data of rainfall, temperature, and humidity, which will be displayed on the dashboard created using Pentaho. The dashboard was displayed on the website localhost that has been built by using the MySQL database as a data storage and Pentaho in conducting the analysis and creation of the dashboard. Forecast for average temperature data in January 2019 also has been done by using Weka. The results of the comparison of original data and forecasting data showed a difference of 0.0573. The comparison of the data shows that Weka can be used as an alternative tool for BMKG of Balikpapan to weather forecasts.